2014
DOI: 10.1021/jp410187q
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Study of Chlorobenzonitrile Isomers: A Survey on the Polymorphism, Pseudosymmetry, and the Chloro···Cyano Interaction

Abstract: The relationships among structural and thermodynamic properties of 2-, 3-, and 4-chlorobenzonitrile were investigated, in the present work, using several experimental techniques (Knudsen effusion, differential scanning calorimetry, and combustion calorimetry) and computational studies. The CN···Cl intermolecular interactions are weaker in 2-chlorobenzonitrile, reflecting a lower enthalpy of sublimation. The two polymorphic forms of 4-chlorobenzonitrile were observed by differential scanning calorimetry and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…[33]. Besides, the molecules of 2-ClBN do not possess an organized structure as the molecular layers Properties of 2-Chlorobenzonitrile: Impact of Biofield Treatment are not perfectly overlapping with each other [34]. It is presumed that biofield energy may be absorbed by the treated 2-ClBN molecules that may lead to increasing the symmetry of 2-ClBN molecules by formation of a symmetrical crystalline long range pattern.…”
Section: Uv-vis Spectroscopic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[33]. Besides, the molecules of 2-ClBN do not possess an organized structure as the molecular layers Properties of 2-Chlorobenzonitrile: Impact of Biofield Treatment are not perfectly overlapping with each other [34]. It is presumed that biofield energy may be absorbed by the treated 2-ClBN molecules that may lead to increasing the symmetry of 2-ClBN molecules by formation of a symmetrical crystalline long range pattern.…”
Section: Uv-vis Spectroscopic Analysismentioning
confidence: 99%
“…3). It was previously reported that 2-ClBN molecules possess CN---Cl intermolecular interactions but these interactions are weak in nature due to which 2-ClBN molecules possess lower enthalpy of sublimation as compared to other isomers [34]. It was hypothesized that biofield energy was absorbed by 2-ClBN molecules that possibly strengthened the intermolecular bonding between chlorine-cyano groups in 2-ClBN molecules.…”
Section: Dsc Analysismentioning
confidence: 99%
“…Meaningful thermochemical comparison can be made with the related fluoro- [154], chloro- [155], and iodo-benzonitriles [156].…”
Section: Issuementioning
confidence: 99%
“…Because of their rich chemistry, cyano substituted benzenes (i.e., benzonitriles) are important intermediates in organic synthesis [1]. While the thermochemical properties of some benzonitriles of interest are known [2][3][4][5][6][7], those for several other simple CN substituted benzenes have yet to be determined. This hinders our knowledge of these aromatic compounds, and prevents the quantitative study of the chemical reactions in which they take part.…”
Section: Introductionmentioning
confidence: 99%